The Many Faces of Wonderful Indonesia: Tourism Brand in 16 Countries Online News Sites - Salamah, Ummi; Yananda, Muhammad Rahmat (UI Scholars Hub, 2020)
Media portrayal has implications for the position of places in the growing regional and international competition for various resources such as tourism, investments and businesses. Public relations campaigns are one of the instruments to counter negative perception and proactively promote a positive image of a place. This research aims to analyze the image of Indonesian tourism brand ‘Wonderful Indonesia’. It focuses on the news from online mainstream media in 16 countries; namely the main target market of Indonesian tourism. News saliency in terms of visibility and sentiment indicate how the media see the tourism brand ‘Wonderful Indonesia’ and the destinations as well. Content analysis was conducted on 336 news articles posted in 4 (four) months. This research also compared ‘Wonderful Indonesia’ with tourism brands belonging to Malaysian (‘Truly Asia’) and Thailand (‘Amazing Thailand’). Less than half of the online news is relevant with the country’s tourism brand and is concentrated within 3 (three) countries: Singapore, Australia and the United Kingdom. The same tendency was also found in other brands, indicating that news placement and news making was not the game in town when it comes to marketing and PR–ing tourism brand